Three dimensional flow simulation over a sharp-crested V-Notch weir - Saadatnejadgharahassanlou, Hamid; Zeynali, Rasoul Ilkhanipour; Gharehbaghi, Amin; Mehdizadeh, Saeid; Vaheddoost, Babak (Elsevier Sci Ltd, 2020)
Thin-plate weirs are widely used to monitor the flow rate in open channels. Thereby, three dimensional (3D) modeling of the flow over a weir in an open channel can be considered as one of the main topics in hydraulic science. In this study, the flow over a sharp-crested v-notch weir (SCVW) is simulated by a 3D numerical model. Laboratory experiments were conducted to monitor and measure the behavior of the SCVW in practice. Finally, the simulated velocity distributions, water surface profiles, and hydraulic jump were compared with those of the experimental data. Due to the turbulent nature of the flow over the SCVW, a Reynolds stress model (RSM) and three types of the k-e turbulence models with the fractional volume of fluid technique (VOF) were used in the analysis. In this respect, the two-phase solution method and dense mesh were used in generating the simulation domain. Results indicated that the RSM exhibited higher accuracy in defining the velocity distribution, complex flow pattern, and predicting the hydraulic jump formation downstream of the SCVW.
Keywords: Experimental model; Numerical simulation; Open channel flow; Two-phase flow; Volume of fluid technique